2020
DOI: 10.2147/opth.s245492
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Subclinical Keratoconus Among Pediatric Egyptian Population with Astigmatism</p>

Abstract: Purpose: To report the prevalence of subclinical keratoconus (KC), and KC suspects, in pediatric Egyptian population with astigmatic error ≥2 diopters (D), with the use of CSO Sirius tomographer. Methods: A cross-sectional study that included all the children aged 6-18 years with an astigmatic error of ≥2 D who attended the pediatric ophthalmology clinic for routine checkups during the period between March 2017 and December 2017 was done. All subjects underwent comprehensive ophthalmic examination, and corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…The prevalence of corneal ectasia is relatively higher among Arabs and people of Eastern Mediterranean descent. 8 , 9 A population-based study conducted in Saudi Arabia revealed an incidence of 20 KC cases per 100,000. 10 Variations in KC epidemiology may be attributed to genetic, environmental, and age-related factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of corneal ectasia is relatively higher among Arabs and people of Eastern Mediterranean descent. 8 , 9 A population-based study conducted in Saudi Arabia revealed an incidence of 20 KC cases per 100,000. 10 Variations in KC epidemiology may be attributed to genetic, environmental, and age-related factors.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Young people are also expected to have a higher prevalence of KC compared to other age groups. 9 , 11 In Egypt, Sidky et al reported that 50.8% of children affected with subclinical KC were between 6 and 12 years of age, and 49.2% were between 12 and 18 years. 9 A multicenter study conducted in 2020 in Riyadh estimated a 4.79% prevalence among the pediatric population aged 6–21 years.…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of keratoconus in Africa was pooled from eight studies [32][33][34][35][36]38,39,43 as these were the only investigations to report the prevalence of keratoconus. The range of prevalences was 0.4%-30.9%.…”
Section: Resultsmentioning
confidence: 99%
“…Only five studies 32,[34][35][36]39 reported the prevalence of keratoconus with gender. Two 32,33 found no significant association with gender, while two studies 35,39 observed significantly higher keratoconus prevalence in males. The overall prevalence among males and females in Africa was pooled from all five studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation